Robustness to secondary extinctions: Comparing trait-based sequential deletions in static and dynamic food webs - Curtsdotter, Alva; Binzer, Amrei; Brose, Ulrich; de Castro, Francisco; Ebenman, Bo; Eklöf, Anna; Riede, Jens O.; Thierry, Aaron; Rall, Björn C. (Basic and applied ecology, 2011)
The loss of species from ecological communities can unleash a cascade of secondary extinctions, the risk and extent of which are likely to depend on the traits of the species that are lost from the community. To identify species traits that have the greatest impact on food web robustness to species loss we here subject allometrically scaled, dynamical food web models to several deletion sequences based on species’ connectivity, generality, vulnerability or body mass. Further, to evaluate the relative importance of dynamical to topological effects we compare robustness between dynamical and purely topological models. This comparison reveals that the topological approach overestimates robustness in general and for certain sequences in particular. Top-down directed sequences have no or very low impact on robustness in topological analyses, while the dynamical analysis reveals that they may be as important as high-impact bottom-up directed sequences. Moreover, there are no deletion sequences that result, on average, in no or very few secondary extinctions in the dynamical approach. Instead, the least detrimental sequence in the dynamical approach yields an average robustness similar to the most detrimental (non-basal) deletion sequence in the topological approach. Hence, a topological analysis may lead to erroneous conclusions concerning both the relative and the absolute importance of different species traits for robustness. The dynamical sequential deletion analysis shows that food webs are least robust to the loss of species that have many trophic links or that occupy low trophic levels. In contrast to previous studies we can infer, albeit indirectly, that secondary extinctions were triggered by both bottom-up and top-down cascades. Der Verlust von Arten in ökologischen Gemeinschaften kann eine Kaskade von sekundären Aussterbeereignissen nach sich ziehen. Das Risiko für das Auftreten und Ausmaß solcher Kaskaden hängt möglicherweise von den Eigenschaften der ausgestorbenen Art ab. Um die Eigenschaften mit dem größten Einfluss auf die Robustheit von Nahrungsnetzen zu identifizieren, nutzen wir allometrisch skalierte, dynamische Nahrungsnetzmodelle und entfernen Arten in verschiedenen, auf der Konnektivität, Generalität oder Vulnerabilität der Art beruhenden Sequenzen. Des Weiteren vergleichen wir Ergebnisse topologischer und dynamischer Modelle, um die verschiedenen Effekte von Topologie und Dynamik auf die Nahrungsnetzrobustheit einschätzen zu können. Dieser Vergleich ergab, dass der topologische Ansatz die Robustheit von Nahrungsnetzen generell und besonders in einigen Sequenzen überschätzt. Im topologischen Modell haben “top-down” Sequenzen keine oder nur sehr wenige Auswirkungen auf die Robustheit der Netze, im dynamischen Modell hingegen können sie einen ebenso großen Effekt haben wie “bottom-up” Sequenzen. Außerdem gibt es im dynamischen Ansatz keine Aussterbe-Sequenzen, die fast oder gar keine sekundären Aussterbeereignisse auslösen. Stattdessen zeigt die am wenigsten schädliche Sequenz im dynamischen Ansatz eine ähnliche Robustheit wie die schädlichste (nicht basale) Sequenz im topologischen Ansatz. Demzufolge kann ein rein topologischer Ansatz zu falschen Rückschlüssen führen, was sowohl die relative als auch die absolute Bedeutung verschiedener Arteigenschaften auf die Robustheit von Nahrungsnetzen angeht. Der dynamische Ansatz zeigt, dass Nahrungsnetze auf das Aussterben von Arten mit vielen trophischen Interaktionen oder niedrigem trophischem Level am wenigsten robust reagieren. Im Gegensatz zu früheren Studien können wir, wenn auch nur indirekt, zeigen, dass sekundäre Aussterbeereignisse sowohl von “top-down” als auch von “bottom-up” Kaskaden ausgelöst werden.